2020
DOI: 10.1101/2020.03.24.20042176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anaesthetic managment and clinical outcomes of parturients with COVID-19: a multicentre, retrospective, propensity score matched cohort study

Abstract: Objective: To analyse the clinical features of COVID-19 parturients, and to compare anaesthetic regimen and clinical outcomes in parturients with or without COVID-19 undergoing cesarean delivery.Methods: Data were extracted from the electronic medical record of 3 medical institutions in Hubei Province, China, from June 1, 2019 to March 20, 2020 according to inclusion and exclusion criteria. After propensity score matching with demographics, the clinical and laboratory characteristics of parturients with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Full text screening then resulted in 148 included articles (Fig 1). [166,167], the USA [168,169], Singapore [170,171], Italy [172,173], Australia [174], Japan [175], Korea [176] and the Netherlands [177]. The mean age of patients was 49 years (SD 11) and where sex data were available, the ratio of males:females was 1.2:1 (10,306:8593).…”
Section: Study Selectionmentioning
confidence: 99%
“…Full text screening then resulted in 148 included articles (Fig 1). [166,167], the USA [168,169], Singapore [170,171], Italy [172,173], Australia [174], Japan [175], Korea [176] and the Netherlands [177]. The mean age of patients was 49 years (SD 11) and where sex data were available, the ratio of males:females was 1.2:1 (10,306:8593).…”
Section: Study Selectionmentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use [23,25,34,39,46,[52][53][54].…”
mentioning
confidence: 99%
“…Some studies showed that perioperative mortality of patients with COVID-19 was very high [30,32,46,[55][56][57] while some studies failed to identify signi cant mortality among patients with COVID-19 undergoing surgical procedures [28,54,58,59].…”
mentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use (16,18,27,32,39,(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that perioperative mortality of patients with COVID-19 was very high (23,25,39,(48)(49)(50) while some studies failed to identify signi cant mortality among patients with COVID-19 undergoing surgical procedures (21,47,51,52).…”
Section: Introductionmentioning
confidence: 99%